Respuesta :

Answer:

Step-by-step explanation:

The remainder theorem says that when you put the integer part of the binomial for the value of x in f(x),  you can solve for the remainder.

f(x) = x^3 - 4x + k is divided by (x - 5) means that 5 is put into f(x)

f(5) = x^3 - 4x + k  now put 5 into x on the right

f(5) = 5^3 - 4(5) + k

f(5) = 125 - 20 + k = 91

f(5) = 105 + k = 91

105 + k = 91                Subtract 105 from both sides

k = 91 - 105

k = -14

168136

Answer: K = 196

Step-by-step explanation:

We are given the equation [tex]f(x) = x^{3} -4x+k[/tex], and we are also given the fact the the 91 is left when the value of x = -5. We have to find the value of k.

1. The first step is to substitute the x for -5.

2. After substituting the x for -5 in all places, ad =91 to make it an equation because we know that 91 will remain. After that, simplify the equation.

-4(-5) becomes 20 because multiplying a negative factor by itself or another negative factor makes the product a positive.

3. Once finished simplifying, add 105 to both sides of the equation in order to get the variable by itself.

1. [tex]f(x) = x^{3} -4x+k[/tex]

   [tex]-5^{3} -4(-5)+k[/tex]

2. [tex]-5x^{3} -4(-5)+k = 91[/tex]

   [tex]-125+20+k=91[/tex]

    [tex]-105+k=91[/tex]

3.  -105 + k = 91

    +105      +105

     [tex]k = 196[/tex]

Hope this helps!